Metabolic syndrome and benign prostatic hyperplasia: An update - Ho-Yin Ngai; Kar-Kei Steffi Yuen; Chi-Man Ng; Cheung-Hing Cheng; Sau-Kwan Peggy Chu (Asian Journal of Urology)
Metabolic syndrome (MetS) is a cluster of metabolic abnormalities related to central adiposity and insulin resistance. Its importance is increasingly recognized as it associates with increased risks of metabolic and cardiovascular diseases. These metabolic aberrations of MetS may lead to development of benign prostatic hyperplasia (BPH) and lower urinary tract symptoms (LUTS) in men. A 26.5%–55.6% prevalence of MetS in men with LUTS was reported in worldwide studies. Although the exact biological pathway is not clear yet, insulin resistance, increased visceral adiposity, sex hormone alterations and cellular inflammatory reactions played significant roles in the related pathophysiological processes. Clinician should recognize the cardiovascular and metabolic impacts of MetS in men with LUTS, early risk factors optimization and use of appropriate medical therapy may possibly alter or slower the progression of LUTS/BPH, and potentially avoid unnecessary morbidities and mortalities from cardiovascular and metabolic diseases for those men. Keywords: Inflammation, Insulin resistance, Lower urinary tract symptoms, Metabolic syndrome X, Prostatic hyperplasia